2009
DOI: 10.1111/j.1468-2494.2009.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

The alkaline pH‐adapted skin barrier is disrupted severely by SLS‐induced irritation

Abstract: The pH of the healthy skin is 5.5 and maintained by many regulatory mechanisms. The pH of the skin care product we use on a daily basis can have an influence on the skin properties. To investigate how the physical properties of skin change after the alkaline or acidic pH of the skin care products are applied on the skin for a long term, we adjusted the pH of the skin care products to 3, 5 and 8 (A, B, C), with glycolic acid and triethanolamine. For 5 weeks the skin care products were applied on 20 healthy subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 15 publications
0
20
1
2
Order By: Relevance
“…In a randomized, controlled, double-blind study, 2 groups of aged residents were nursed over 7 weeks -taking the age-related decelerated epidermal turnover time into account -with skin care products adjusted to a pH of 4.0 (group A) or a pH of 6.0 (group B). In contrast to Kim et al [49] , we discovered that skin hydration was significantly improved by application of the acidic products (p = 0.005) but not by treatment with cosmetics Table 3. Skin flora results before (baseline) and after treatment in relation to the study group adjusted to a pH of 6.0 (p = 0.161).…”
Section: Discussioncontrasting
confidence: 52%
“…In a randomized, controlled, double-blind study, 2 groups of aged residents were nursed over 7 weeks -taking the age-related decelerated epidermal turnover time into account -with skin care products adjusted to a pH of 4.0 (group A) or a pH of 6.0 (group B). In contrast to Kim et al [49] , we discovered that skin hydration was significantly improved by application of the acidic products (p = 0.005) but not by treatment with cosmetics Table 3. Skin flora results before (baseline) and after treatment in relation to the study group adjusted to a pH of 6.0 (p = 0.161).…”
Section: Discussioncontrasting
confidence: 52%
“…Biophysical parameters in our study did not reflect differences between participants with SS and NSS, and did not parallel the conclusion with regard to the skin barrier. Slightly lower baseline SC hydration values were found, which reached statistical significance in one study, but higher baseline values have been reported . TEWL at baseline is mainly shown to be higher in those with SS, but rarely reaches significance …”
Section: Antibody Specificationsmentioning
confidence: 86%
“…The skin pH may be affected by internal factors such as sebum, hydration, and anatomical regions and external factors such as environments and habits of using detergents and cosmetics in everyday life [15]. The skin sebum content neutralizes alkali and prevents dry skin to act as an important factor in controlling skin moisture contents [15,16]. In the results of this study, there was a significantly higher sebum secretion in measured regions, the centre of the forehead, and the glabella in summer than in winter.…”
Section: Discussionmentioning
confidence: 99%